Preferences of patients and clinicians for treatment of Graves' disease: a discrete choice experiment. Issue 6 (4th May 2021) - van Kinschot, Caroline M J; Soekhai, Vikas R; de Bekker-Grob, Esther W; Visser, W Edward; Peeters, Robin P; van Ginhoven, Tessa M; van Noord, Charlotte
Abstract : Objective: Treatment options for Graves' disease (GD) consist of antithyroid drugs (ATD), radioactive iodine (RAI) and total thyroidectomy (TT). Guidelines recommend to discuss these options with patients, taking into account patients' preferences. This study aims to evaluate and compare patients' and clinicians' preferences and the trade-offs made in choosing treatment. Design and methods: A discrete choice experiment (DCE) was performed with GD patients with a first diagnosis or recurrence in the previous year, and with clinicians. Participants were offered hypothetical treatment options which differed in type of treatment, rates of remission, severe side effects, permanent voice changes and hypocalcemia. Preference heterogeneity was assessed by latent-class analysis. Results: In this study, 286 (82%) patients and 61 (18%) clinicians participated in the DCE. All treatment characteristics had a significant effect on treatment choice ( P < 0.05). Remission rate was the most important determinant and explained 37 and 35% of choices in patients and clinicians, respectively. Both patients and clinicians preferred ATD over surgery and RAI. A strong negative preference toward RAI treatment was observed in a subclass of patients, whereas clinicians preferred RAI over surgery. Conclusion: For both patients and clinicians, remission rate was the most important determinant of treatment choice and ATD was the most preferred treatment option. Patients had a negative preference toward RAI compared to alternatives, whereas clinicians preferred RAI over surgery. Clinicians should be aware that their personal attitude toward RAI differs from that of their patients. This study on patients' and clinicians' preferences can support shared decision making and thereby improve clinical treatment.